1999
DOI: 10.1007/s002800050989
|View full text |Cite
|
Sign up to set email alerts
|

The effect of antimicrotubule agents on signal transduction pathways of apoptosis: a review

Abstract: Disruption of microtubule structure by antimicrotubule drugs results in induction of tumor suppressor gene p53 and inhibitor of cyclin-dependent kinases, p21WAF1/CIP1 (p21), and activation/inactivation of several protein kinases including Ras/Raf, PKC/PKA I/II, MAP kinases, and p34cdc2. These protein kinases are associated directly or indirectly with phosphorylation of bcl-2. Phosphorylation of bcl-2 and the elevations of p53 and p21 lead to apoptosis. New pathways of antitumor agents could be directed at this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
231
3
8

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 351 publications
(259 citation statements)
references
References 64 publications
17
231
3
8
Order By: Relevance
“…We show that GIST-S cells are resistant to docetaxel alone but in combination with MP470 are sensitive to synergistic cell killing. Docetaxel inhibits tumor growth by induction of microtubule stabilization, promotion of BCL-2 phosphorylation and inactivation leading to p53-and p21-driven apoptosis (Haldar et al, 1997;Wang et al, 1999). As GIST patients overexpress BCL-2 (80%), the strategy of targeting KIT/AXL and BCL-2 together appears feasible.…”
Section: Discussionmentioning
confidence: 99%
“…We show that GIST-S cells are resistant to docetaxel alone but in combination with MP470 are sensitive to synergistic cell killing. Docetaxel inhibits tumor growth by induction of microtubule stabilization, promotion of BCL-2 phosphorylation and inactivation leading to p53-and p21-driven apoptosis (Haldar et al, 1997;Wang et al, 1999). As GIST patients overexpress BCL-2 (80%), the strategy of targeting KIT/AXL and BCL-2 together appears feasible.…”
Section: Discussionmentioning
confidence: 99%
“…Induction of p53 and p21 by antimicrotubule agents has been considered to be one mechanism involved in the apoptotic process in cancer cells (Blagosklonny et al, 1995;Barboule et al, 1997;Torres and Horwitz, 1998;Wang et al, 1999b). To explore whether vinorelbine and paclitaxel are able to induce p21 expression in AD and AI cells that are deficient in p21, and the possible differences between AD and AI cells in expression of p53 and p21 in response to treatments with vinorelbine or paclitaxel, the resultant levels of p53 and p21 were determined by Western blotting.…”
Section: Induction Of P53 and P21 Wafi/c1p1 Expression By Vinorelbinementioning
confidence: 99%
“…In contrast to paclitaxel, vinorelbine binds microtubules and prevents their polymerisation, thus interfering with mitosis (Krikorian and Breillout, 1991). Previous studies have demonstrated that independent of the type of effect by the antimicrotubule agent on microtubule assembly (polymerisation or depolymerisation), these drugs exhibit the ability to promote apoptosis in cancer cells (Wang et al, 1999bBudman et al, 2000;Charles et al, 2001;Fan et al, 2001;Liu et al, 2001). One of mechanisms of vinorelbine-induced apoptosis is thought to be the upregulation of p21 and p53.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, c-Src has been found to be highly activated in colon cancer metastasized to the liver (Mao et al, 1997) and mutation in the regulatory domain of c-Src has been reported as a mechanism of Src activation in human colon cancer (Irby et al, 1999). Although a number of signal transduction pathways toward Bcl-2 phosphorylation have been reported as an apoptotic mechanism induced by taxanes (Wang et al, 1999), the role of Src in these processes has yet to be determined. Src transduces a variety of signals to downstream signal transduction cascades including Ras (Brown and Cooper, 1996).…”
mentioning
confidence: 99%